Observations of the chemical composition of stratospheric aerosol particles. (22nd November 2013) - Murphy, D. M.; Froyd, K. D.; Schwarz, J. P.; Wilson, J. C.
Abstract Recent instrumentation can distinguish various types of aerosol particles in the stratosphere and determine their relative abundance. In the background lower stratosphere between major volcanic eruptions, most particles are either relatively pure sulphuric acid, sulphuric acid with material from ablated meteoroids or mixed organic‐sulphate particles that originated in the troposphere. The meteoritic iron and magnesium appear to be dissolved whereas the aluminum and silicon appear to be inclusions. Most stratospheric aerosol mass is liquid sulphuric acid and associated water, but a large fraction of particles contain either inclusions of meteoritic elements such as silicon or organic material that is probably effloresced or glassy. These solid phases could have large but unknown implications for the ability of particles to act as freezing nuclei for polar stratospheric clouds. Internally mixed black carbon is a measurable but very small component of the stratospheric aerosol by mass. Despite their importance for heterogeneous chemistry, there are few quantitative measurements of halogens in stratospheric particles.